Sensitivity and specificity of PS/AA‐modified nanoparticles used in malaria detection. Issue 4 (11th June 2013) - Thiramanas, Raweewan; Jangpatarapongsa, Kulachart; Asawapirom, Udom; Tangboriboonrat, Pramuan; Polpanich, Duangporn
Summary Polystyrene (PS) nanoparticle (NP) copolymerized with acrylic acid (AA) and coloured monomer, i.e. 2, 3, 6, 7‐tetra(2, 2′‐bithiophene)‐1, 4, 5, 8‐naphthalenetetracarboxylic‐N, N′‐di(2‐methylallyl)‐bisimide (ALN8T), was synthesized via the miniemulsion polymerization. Before applying for malaria antigen detection, the blue NP was conjugated with human polyclonal malaria IgG antibody (Ab) specific to Plasmodium falciparum. For the conjugation, three methods, i.e. physical adsorption, covalent coupling and affinity binding via streptavidin (SA) and biotin interaction, were employed. The optimum ratio of Ab to NPs used in each immobilization procedure and the latex agglutination test based on the reaction between Ab conjugated NPs and malaria patient plasma were investigated. All Ab–latex conjugates provided the high sensitivity for the detection of P. falciparum malaria plasma. The highest specificity to P. falciparum was obtained from using Ab–NPs conjugated via the SA–biotin interaction.